The Representation of Liberal Feminism in Barbie (2023) Based on Rosemarie Tong’s Theory - Firda Azzahra; Irma Rahmawati (Calakan : Jurnal Sastra, Bahasa, dan Budaya, 2026)
This study examines the representation of liberal feminism in Barbie (2023) using Rosemarie Tong’s theory, with female autonomy as the main analytical concept. Using a descriptive qualitative method, the study analyzes selected dialogues, scenes, and actions performed by the character Barbie, collected through repeated viewing, note-taking, and screenshot documentation. The data are organized through an analytical framework of social expectations and identity transformation before being interpreted through Tong’s principles of freedom of choice, self-determination, and independence. The findings show that liberal feminism is primarily represented through Barbie’s gradually developing autonomy as she exercises freedom of choice, builds self-determination, and demonstrates independence in defining herself according to her own values. Social expectations, expressed through unrealistic standards, restrictive gender roles, and objectifying cultural norms, function as external pressures that push Barbie to question her assigned identity and strengthen her autonomy. This process culminates in an identity transformation moving from an identity crisis, through self-understanding, toward a self-defined identity. The study concludes that Barbie (2023) represents liberal feminism through the interrelation of female autonomy, social expectations, and identity transformation, with autonomy as the central representation and the other elements providing the context and process through which it is achieved.